Usage of social media to enhance job performance and reduce stress in organisation / Ahlam Abdul Aziz ... [et al.] - Abdul Aziz, Ahlam; Bolong, Jusang; Hj. Hassan, Md Salleh; Hassan, Hamisah (Institute of Research Management Innovation (IRMI), 2015)
Social media is frequently used as a tool to help employees perform their jobs in the organisation. The use of media technologies can help employees to reduce their stress and improve their job performance for their key performance index. This study aims to describe the use of Facebook as the mediating factor to reduce stress and enhance job performance. The Technology Acceptance Model was applied in this study as justifications of encouraging employees to adapt Facebook in helping them with their tasks through perceive ease of use and perceive usefulness. This study also indicates that hypotheses on usage of Facebook does not mediate the relationship between both perceive usefulness and perceive ease of use on employees 'job performance.